Preparation and Characterization of (125)I Labeled Bovine Serum Albumin - Ashwitha Rai, K. S. (Indian J Pharm Sci, 2015)
Bovine serum albumin is a model protein, which has been conventionally used as protein standard and in many areas of biochemistry, pharmacology and medicine. Radioiodination procedure for bovine serum albumin employing chloramine-T as an oxidant with slight modification was evaluated critically to establish the optimal conditions for the preparation of radiolabeled tracer ((125)I-BSA) with required specific activity without impairing the immune reactivity and biological activity. Optimized radioiodination procedure involving 10 µg of chloramine-T along with 20 µg of sodium metabisulphite with 60 seconds incubation at 2° yielded (125)I-BSA with high integrity.